Taking charge of breast cancer - Ericksen, Julia A., 1941- (University of California Press, 2008)
Vividly showcasing diverse voices and experiences, this book illuminates an all-too-common experience by exploring how women respond to a diagnosis of breast cancer. Drawing from interviews in which women describe their journeys from diagnosis through treatment and recovery, Julia A. Ericksen explores topics ranging from women's trust in their doctors to their feelings about appearance and sexuality. She includes the experiences of women who do not put their faith in traditional medicine as well as those who do, and she takes a look at the long-term consequences of this disease. What emerges from her powerful and often moving account is a compelling picture of how cultural messages about breast cancer shape women's ideas about their illness, how breast cancer affects their relationships with friends and family, why some of them become activists, and more. Ericksen, herself a breast cancer survivor, has written an accessible book that reveals much about the ways in which we narrate our illnesses and about how these narratives shape the paths we travel once diagnosed.